Study of a saturation point to establish the doping density limit of silicon with graphene oxide. (15th June 2019) - Ain, Qura Tul; Bano, N.; Al-Modlej, Abeer; Alshammari, Abeer; Hussain, I.; Anjum, Muhammad Naeem
Abstract: An extensive study of Si-doped graphene oxide (GO) is presented to explore the material properties that are important for enabling a wide range of optoelectronic devices. We find a saturation point to establish the doping density limit for the doping GO with silicon. FESEM and EDX element mapping analysis show the distribution of the silicon atoms on the GO surface. The Fourier-transform infrared spectra reveal that the silicon atoms are incorporated into the GO lattice with Si-C, Si-O-Si, and Si-OH configurations. The fluorescence emission spectra of Si-GO indicate that the emission intensity increases with doping and is two times more intense with 8% Si doping than the as-grown GO. Extensive systematic measurements are performed to confirm the saturation point of Si doping.